SAVING THE UTERUS; OUR EXPERIENCE IN UTERINE ARTERY EMBOLIZATION FOR ACQUIRED UTERINE VASCULAR ABNORMALITIES - Masood, Laiba; Amin Khan, Zahid; Ahmed, Muhammad Shozab; Rana, Atif Iqbal (Journal of Ayub Medical College Abbottabad, 2022)
Background: Acquired uterine vascular abnormalities are a rare cause of potentially life-threatening bleeding. These include uterine artery pseudoaneurysms (UAP)and acquired arteriovenous malformations. The objective of this study was to describe our experience with the diagnosis of acquired uterine vascular abnormalities and its treatment with uterine preservation. It was a retrospective cohort study. Methods: Eight patients were enrolled from the hospital database who presented to our Interventional Radiology department from April 2017 to March 2021 for uterine artery embolisation (UAE) with a history of iatrogenic/acquired uterine vascular abnormalities confirmed on imaging. These included two patients with uterine artery pseudoaneurysm (PA) concurrently with arteriovenous malformation (AVM), one with uterine artery PA and five having uterine AVMs. Embolisation agents used were histoacryl glue, lipiodol, PVA particles, and gelfoam slurry. Medical records, imaging studies, and telephonic contact with patients were assessed for patient presentation, intraprocedural details, and follow up to record treatment success. Statistical analysis was performed using descriptive statistics. Results: Bilateral UAE was performed in six patients, while two patients underwent unilateral UAE. Three of the patients presented with life-threatening bleeds requiring multiple transfusions. Clinical as well as angiographic success was achieved in all patients with immediate control of haemorrhage. No complications were observed during follow-up. Two of the patients were able to conceive normally within one year, though it resulted in a miscarriage. Conclusion: Acquired/iatrogenic uterine vascular abnormalities are a rare but important cause of life-threatening haemorrhage that can be expertly managed and successfully treated using UAE, which is rapid, safe, and minimally invasive, with the added advantage fertility preservation.